Marsilio Ficino: his theology, his philosophy, his legacy - Allen, Michael J. B. (Brill's studies in intellectual history, 2002)
This volume consists of 21 essays on Marsilio Ficino (1433-99), the Florentine scholar, philosopher and priest who was the architect of Renaissance Platonism and whose long-lasting influence on philosophy, love and music theory, medicine and magis extended across Europe